New light on the systematics of fungi associated with attine ant gardens and the description of escovopsis kreiselii sp nov - Meirelles, Lucas A. [UNESP]; Montoya, Quimi V. [UNESP]; Solomon, Scott E.; Rodrigues, Andre [UNESP] (Public Library Science, 2015)
Since the formal description of fungi in the genus Escovopsis in 1990, only a few studies have focused on the systematics of this group. For more than two decades, only two Escovopsis species were described; however, in 2013, three additional Escovopsis species were formally described along with the genus Escovopsioides, both found exclusively in attine ant gardens. During a survey for Escovopsis species in gardens of the lower attine ant Mycetophylax morschi in Brazil, we found four strains belonging to the pink-colored Escovopsis clade. Careful examination of these strains revealed significant morphological differences when compared to previously described species of Escovopsis and Escovopsioides. Based on the type of conidiogenesis (sympodial), as well as morphology of conidiogenous cells (percurrent), non-vesiculated conidiophores, and DNA sequences, we describe the four new strains as a new species, Escovopsis kreiselii sp. nov. Phylogenetic analyses using three nuclear markers (Large subunit RNA; translation elongation factor 1-alpha; and internal transcribed spacer) from the new strains as well as available sequences in public databases confirmed that all known fungi infecting attine ant gardens comprise a monophyletic group within the Hypocreaceae family, with very diverse morphological characteristics. Specifically, Escovopsis kreiselii is likely associated with gardens of lower-attine ants and its pathogenicity remains uncertain.